The Discourse of Covids-19 Pandemic Policies in Indonesia - Dr. Nurhayati; Peter Suwarno (Master Program in Linguistics, Diponegoro University, 2020)
Since covid-19 has become pandemic, an abundance of coronavirus news fills the mass media throughout the world. The pandemic is constructed verbally from various perspectives for many purposes. In Indonesia, the discourse of the pandemic is not only about the disease, but also about other social issues related to the pandemic. Through certain discourses, the text producers may present various meanings. This study purposes to uncover social meanings presented in the discourses constructed by the mass media regarding the Indonesian government policies to cut the Covid-19 pandemic. Using a critical discourse analysis approach, the researchers analyze clauses containing three terms: Isolasi Mandiri, PSBB, and local lockdown from 28 downloaded texts. The focus of analysis is on the selection of lexico-grammar used to represent the policies to cut the chain of the pandemic. The result shows that there are three patterns in positioning participants regarding who has to take the responsibility for the implementation of the policies. The discourse about Isolasi Mandiri position residents as a party who has to be responsible and the government was positioned as the controller. The discourse of PSBB has positioned the government as a party that conducts and controls the implementation of the policies. The discourse of local lockdown represented that the policy was only as planning urged by the NGO and has not been conducted by the government. The context influencing the discourse is the socio-economic context. The discourses also show that the way media represented the policies is in line with the government agenda.